Association of vasomotor symptoms and sleep apnea risk in midlife women. Issue 4 (April 2018) - Gao, Catherine C.; Kapoor, Ekta; Lipford, Melissa C.; Miller, Virginia M.; Schroeder, Darrell R.; Mara, Kristin C.; Faubion, Stephanie S.
Abstract: Objective: The aim of the study was to determine the association between self-reported vasomotor symptoms (VMS) and obstructive sleep apnea (OSA) risk. Methods: The STOP-BANG to evaluate OSA and Menopause Rating Scale (MRS) were administered to 2, 935 women seen in the Women's Health Clinic at Mayo Clinic in Rochester, MN, between May 2015 and December 2016. Of these, 1, 691 women were included in the analysis. Total MRS and VMS ratings were compared using logistic regression, with age, smoking, and body mass index (BMI) included as covariates between women at intermediate/high risk versus low risk for OSA. Results: Total MRS scores were significantly higher in women with intermediate/high-risk OSA scores versus those with low-risk scores [mean (SD): 16.8 (8.0) vs 12.9 (7.0), P  < 0.001]. Women at intermediate/high OSA risk were older, had more education, self-reported hypertension, BMI >35 kg/m 2, and were less likely to be married or employed. Self-reported severe/very severe VMS were significantly associated with intermediate/high risk versus low risk for OSA (26.6% vs 15.0%; P  < 0.001). After adjusting for age, BMI, smoking status, and self-reported hypertension, the odds of having intermediate/high risk for OSA were 1.87 times higher for those with severe/very severe VMS compared with those with none/mild/moderate VMS (95% CI, 1.29-2.71, P  < 0.001). This association persisted upon subgroup analysis based on BMI <25 kg/m 2 (odds ratio 2.15; 95% CI, 1.12-4.16, P = 0.022). Conclusions: Self-reported severe/very severe VMS were associated with intermediate/high risk for OSA in midlife women, even in women with BMI <25 kg/m 2 . Given the limitations of the STOP-BANG tool, OSA risk may, however, have been overestimated.